Effects of liposomal nasal spray with vitamins A and E on allergic rhinitis - Lauriello, Maria (Acta Otorhinolaryngol Ital, 2020)
The aim of this study was to investigate the relationship between nasal obstruction and nasal cytology in patients with allergic rhinitis (AR) treated with a liposomal based nasal spray containing vitamins A and E. This is a prospective double-blind, controlled study. A total of 106 patients with AR, who rejected anti-allergic therapy, were randomly divided into two groups: G (study group, n = 53) received liposomal nasal spray and C (control group, n = 53) received 0.9% sodium chloride solution nasal spray. Both nasal sprays were applied two times a day, in the morning and at night, in both nasal cavities. The study lasted for 30 days. The first ENT evaluation was performed the first day (T0) and the second evaluation was performed at the end of the study (T1). Symptoms (SNOT-22 test with VAS) and signs (nasal cytology) of both groups were recorded at T0 and T1. Liposomal nasal spray was effective in improving both nasal symptoms and cytology in patients suffering from perennial AR. Treatment with liposomal nasal spray with vitamins A and E was followed by a significant improvement of VAS scale (p < 0.0001), a significant decrease in SNOT-22 (p < 0.0001) and a significant decrease in inflammatory cell count (p < 0.0001). In conclusion, our study provides evidence that liposomal nasal spray improves the nasal symptoms of AR. The patients were compliant to this therapy because of limited side effects. The reduction in inflammatory cells count was remarkable and confirmed the close association between eosinophil infiltration and nasal airflow impairment. These results may have implications for clinical practice.